Condensable Particulate Matter Removal and Its Mechanism by Phase Change Technology During Wet Desulfurization Process - Hui Tong; Yun Xu; Qiangqiang Ren; Hao Wu; Linzhi Shen; Menglong Sun; Hongmin Yang (Separations)
Limestone-gypsum wet flue gas desulfurization (WFGD) played a key role in SOx removal and clean emissions. However, it would also affect the condensable particulate matter (CPM) removal and compositions. The effects of the WFGD system on the removal of CPM and the contents of soluble ions in CPM were investigated in a spray desulfurization tower at varied conditions. The results indicate that the emission concentration of CPM decreased from 7.5 mg/Nm3 to 3.7 mg/Nm3 following the introduction of cold water spray and hot alkali droplet spray systems. This resulted in a CPM reduction rate of approximately 51%, reducing the percentage of CPM in total particulate matter and solving the problem of substandard particulate matter emission concentrations in some coal-fired power plants. The concentrations of NO3−, SO42−, and Cl− among the soluble ions decreased by 41–66.6%. As the liquid-to-gas ratio of the cold water spray and hot alkali droplet spray increased, CPM came into contact with more spray, which accelerated dissolution and chemical reactions. Consequently, the CPM emission concentration decreased by 17.4–19%. The liquid-to-gas ratio has a great effect on the ion concentrations of NO3−, SO42−, Cl− and NH4+, with a decrease of 28–66%. The temperatures of the cold water spray and the hot alkali droplet spray primarily affect the ionic concentrations of SO42− and Ca2+, leading to a decrease of 32.3–51%. When the SO2 concentration increased from 0 mg/Nm3 to 1500 mg/Nm3, large amounts of SO2 reacted with the desulfurization slurry to form new CPM and its precursors, the CPM emission concentration increased by 57–68.4%. This study addresses the issue of high Concentration of CPM emissions from coal-fired power plants in a straightforward and efficient manner, which is significant for enhancing the air quality and reducing hazy weather conditions. Also, it provides a theoretical basis and technical foundation for the efficient removal of CPM from actual coal-fired flue gas.